Discriminative and Criterion Validity of the Autism Spectrum Identity Scale (ASIS). - McDonald, T. (Journal of Autism & Developmental Disorders, 2017)
Individuals on the autism spectrum face stigma that can influence identity development. Previous research on the 22-item Autism Spectrum Identity Scale (ASIS) reported a four-factor structure with strong split-sample cross-validation and good internal consistency. This study reports the discriminative and criterion validity of the ASIS with other measures. Adults (n = 1139) who have, or identify with, an autism spectrum diagnosis took a nationally distributed online survey that also included demographic questions and measures for stigma, self-esteem, and quality of life (QoL). All four ASIS factors discriminated from measures of stigma and self-esteem. The ASIS also showed good criterion validity with the factors of Positive Difference and Changeability demonstrating widespread relationships with subjective quality of life in the expected directions.